2012
DOI: 10.1080/13825585.2011.629288
|View full text |Cite
|
Sign up to set email alerts
|

Age benefits in everyday prospective memory: The influence of personal task importance, use of reminders and everyday stress

Abstract: The present diary study examined everyday prospective memory tasks in younger and old adults and explored the role of personal task importance, use of reminders and everyday stress as possible correlates of age-related prospective memory performance in everyday life. Results revealed an age benefit in everyday prospective memory tasks. In addition, task importance was identified as a critical moderator of age-related prospective memory performance. More frequent use of reminders and lower levels of stress, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
91
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 21 publications
14
91
2
Order By: Relevance
“…Therefore, in the current study, the nonstudent group would need very high estimates of task importance to exceed those expected from the college group. In contrast, we would predict no difference in importance ratings between young college students and older adults because that outcome would replicate past findings (Freeman and Ellis 2003;Ihle et al 2012). …”
Section: Predictions For Young Versus Older Adultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Therefore, in the current study, the nonstudent group would need very high estimates of task importance to exceed those expected from the college group. In contrast, we would predict no difference in importance ratings between young college students and older adults because that outcome would replicate past findings (Freeman and Ellis 2003;Ihle et al 2012). …”
Section: Predictions For Young Versus Older Adultsmentioning
confidence: 63%
“…However, their young adult sample was composed entirely of college students. Similarly, Ihle et al (2012) also found no age-related difference in importance ratings for real prospective memory tasks, although again their young adult sample consisted of ''mostly'' undergraduate students. Thus, research has shown two null results for age effects on importance ratings for real-life prospective memory tasks despite prior demonstrations of the effect for experimenterassigned tasks (e.g., Kvavilashvili and Fisher 2007;Patton and Meit 1993).…”
Section: Predictions For Young Versus Older Adultsmentioning
confidence: 84%
See 3 more Smart Citations